Convenience Food Lifestyle Segments – A Study of Delhi - NCR - Dhillon, Supriya; Munjal, Neetu (Indian Journal of Marketing, 2022)
Over the past few decades, several socio-cultural, demographic, economic, and lifestyle changes have occurred, which in turn have modified the food-related lifestyles of people. Convenience foods such as ready-to-eat and ready-to-cook products are the outcome of this shift from hunter-gatherers to convenience-seeking customers. The present study aimed at segmenting the convenience food market, particularly ready-to-cook food, based on food-related lifestyles. A segmentation study based on cluster analysis was applied to 16 identified food-related lifestyle factors resulting in four convenience food lifestyle segments – adventurous consumers (38.6%), uninvolved consumers (28.60%), relaxed consumers (25.23%), and convenience seekers (7.67%). In particular, convenience seekers and adventurous consumers can be treated as a target market for convenience food in India. The current study will assist food marketers in identifying the target segments for RTC food by profiling the RTC food consumer lifestyle segments.